2009
DOI: 10.1073/pnas.0813108106
|View full text |Cite
|
Sign up to set email alerts
|

Cyp26 enzymes function in endoderm to regulate pancreatic field size

Abstract: The control of organ size and position relies, at least in part, upon appropriate regulation of the signals that specify organ progenitor fields. Pancreatic cell fates are specified by retinoic acid (RA), and proper size and localization of the pancreatic field are dependent on tight control of RA signaling. Here we show that the RAdegrading Cyp26 enzymes play a critical role in defining the normal anterior limit of the pancreatic field. Disruption of Cyp26 function causes a dramatic expansion of pancreatic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…Conversely, blocking CXCR4 signaling with the inhibitor AMD3100 resulted in disrupted angioblast migration and reduced Pdx1 expression. Although it is suggested that angioblasts might induce PDX1 in a paracrine manner via retinoic acid, as studies in both zebrafish and chicks have proposed (Kumar et al, 2003;Kinkel et al, 2009), the exact nature of the vascular signal in question still remains elusive.…”
Section: Blood Vessel Signals During Pancreatic Specificationmentioning
confidence: 99%
“…Conversely, blocking CXCR4 signaling with the inhibitor AMD3100 resulted in disrupted angioblast migration and reduced Pdx1 expression. Although it is suggested that angioblasts might induce PDX1 in a paracrine manner via retinoic acid, as studies in both zebrafish and chicks have proposed (Kumar et al, 2003;Kinkel et al, 2009), the exact nature of the vascular signal in question still remains elusive.…”
Section: Blood Vessel Signals During Pancreatic Specificationmentioning
confidence: 99%
“…However, in chick explants, the effect of RA on promoting pancreas requires mesoderm suggesting that the RA is also acting on the mesoderm to drive pancreas differentiation [77]. Excess RA is able to drive an anterior expansion of the Pdx1 expression domain in zebrafish demonstrating that it is both necessary and sufficient for pancreas formation [124].…”
Section: Retinoic Acid and The Pancreasmentioning
confidence: 99%
“…This provides a model where retinoic acid is necessary for formation of the pancreas and also creates a negative feedback loop that regulates pancreas size [124]. Size regulation by RA in the mouse pancreas, in particular the β-cell and α-cell mass, continues in the adult because vitamin A deficiency results in reduced mass that is subsequently restored when normal vitamin A levels are restored [127] …”
Section: Retinoic Acid and The Pancreasmentioning
confidence: 99%
“…RA may also act at later steps of specification of pancreatic endocrine cell lineages (Martin et al, 2005;Ostrom et al, 2008). Recent work indicates that RA may act more globally to coordinate the position of endoderm-derived organs along the foregut and midgut A-P axis (Bayha et al, 2009), and that CYP26 enzymes may restrict the extent of RA signalling and set up the limit of the pancreatic field (Kinkel et al, 2009). …”
Section: Ra Signalling and Pancreas Developmentmentioning
confidence: 99%